Balanced Scorecard Performance Evaluation Model for Waqf Institution - Djalil, Noviendri; Anwar, Saiful (ZISWAF, 2022)
Nazir Professional supports the management and utilization of productive waqf in Indonesia with measurable performance and competence. This study aimed to contribute to the Indonesian Waqf Board in evaluating Nazir's performance and competence in managing productive waqf through Key Performance Indicators (KPI). A descriptive qualitative analysis was conducted on previous studies to examine Nazir's performance and competence through KPIs based on the Balanced Scorecard. KPIs and periodic evaluations could make Nazir work more productively and professionally to increase the growth of productive waqf. Furthermore, the Nazirs could use the KPI performance, and competency assessment model proposed to the Indonesian Waqf Board to standardize its performance and competency assessments. The proposed model is hoped to be refined through further evaluation in the future.